Європейськість сучасної української моди - Цимбалюк, О. (Інститут народознавства НАН України, 2008)
The Ukrainian Mode exists really on a level of the folk and elite artistic tradition. The Ukrainian Mode declares about itself in the world with the individual flashes. It is the part of World Mode. Today and in the future the Ukrainian Mode the essential attention gives to the new technologies. The Lviv School of the modern design of clothes active develops the associative tendencies of Ukrainian Mode on the base of the folk traditions.